Immunisation with a multivalent, subunit vaccine reduces patent infection in a natural bovine model of onchocerciasis during intense field exposure. - Benjamin L Makepeace; Siv Aina Jensen; Sandra J Laney; Charles K Nfon; Leo M Njongmeta; Vincent N Tanya; Steven A Williams; Albert E Bianco; Alexander J Trees (Public Library of Science (PLoS), 2009)
Human onchocerciasis, caused by the filarial nematode Onchocerca volvulus, is controlled almost exclusively by the drug ivermectin, which prevents pathology by targeting the microfilariae. However, this reliance on a single control tool has led to interest in vaccination as a potentially complementary strategy. Here, we describe the results of a trial in West Africa to evaluate a multivalent, subunit vaccine for onchocerciasis in the naturally evolved host-parasite relationship of Onchocerca ochengi in cattle. Naïve calves, reared in fly-proof accommodation, were immunised with eight recombinant antigens of O. ochengi, administered separately with either Freund's adjuvant or alum. The selected antigens were orthologues of O. volvulus recombinant proteins that had previously been shown to confer protection against filarial larvae in rodent models and, in some cases, were recognised by serum antibodies from putatively immune humans. The vaccine was highly immunogenic, eliciting a mixed IgG isotype response. Four weeks after the final immunisation, vaccinated and adjuvant-treated control calves were exposed to natural parasite transmission by the blackfly vectors in an area of Cameroon hyperendemic for O. ochengi. After 22 months, all the control animals had patent infections (i.e., microfilaridermia), compared with only 58% of vaccinated cattle (P = 0.015). This study indicates that vaccination to prevent patent infection may be an achievable goal in onchocerciasis, reducing both the pathology and transmissibility of the infection. The cattle model has also demonstrated its utility for preclinical vaccine discovery, although much research will be required to achieve the requisite target product profile of a clinical candidate.